FENOMENA PENGGUNAN MEDIA SOSIAL INSTAGRAM SEBAGAI KOMUNIKASI PEMBELAJARAN AGAMA ISLAM OLEH MAHASISWA FISIP UNIVERSITAS RIAU - Meutia Puspita Sari; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The use of instagram as a learning communication is a new phenomenon that exists in utilizing social media. Social media that has a function as a medium of communication and media sharing, is used as a communication learning by students of FISIP Universitas Riau in fulfilling the need for information and knowledge of Islam religion. This study aims to determine the motives, communication experience, and behavioral changes of learning outcomes conducted by students of FISIP University of Riau as a user of social media instagram.This research uses qualitative research method with phenomenology approach. The subjects were chosen using purposive technique in the form of 4 students of FISIP Universitas Riau and 4 significant others. To obtain data, the author uses three data collection techniques, namely participant observation, in-depth interviews, and documentation. This research uses data analysis technique of phenomenology research according to Creswell, using observational persistence technique, extension of participation, and reference adequacy.The results showed that the use of instagram as a communication learning by FISIP students, University of Riau is influenced by 2 motifs, the first motive of the past (because motive) belonging to the motive sosiogenetis, in the form of curious motifs, motives of need for value, self-esteem motive and the need for Looking for the identity and motive of the future (in order to motives) belonging to the theogenetic motif as a medium of propagation information, as a motivating medium (other people) and as a source of information. Communication experience perceived by users of instagram as communication learning by FISIP students of Universitas Riau is a pleasant communication experience where can exchange information of da'wah; Make new friends; And gain a sense of change after learning religious knowledge and unpleasant experiences with negative comments. Finally, the use of instagram as a communication of Islamic learning resulted in a change in attitude and behavior that is in cognition, affection, and konasi or psychomotor instagram users in the community.Key Word: Fenomenology, Instagram, Communication learning